2021
DOI: 10.1038/s41438-021-00461-x
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed mutagenesis identified the key active site residues of alcohol acyltransferase PpAAT1 responsible for aroma biosynthesis in peach fruits

Abstract: The aroma of peach fruit is predominantly determined by the accumulation of γ-decalactone and ester compounds. A previous study showed that the biosynthesis of these aroma compounds in peach fruit is catalyzed by PpAAT1, an alcohol acyltransferase. In this work, we investigated the key active site residues responsible for γ-decalactone and ester biosynthesis. A total of 14 candidate amino acid residues possibly involved in internal esterification and 9 candidate amino acid residues possibly involved in esterif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
(65 reference statements)
0
18
0
Order By: Relevance
“…In the present study, PaAAT1 not only contained two common HTMCD (165–169 residues) in motif 1 and DVGWG (386–340 residues) conserved motifs in motif 7 but also contained the AAT-specific conserved motif LVYYYPLAGR (74–83 residues) in motif 8 ( Figures 1 , 2 ). Even so, residue differences might significantly alter the catalytic activity of the AAT protein and dramatically affected the esterification reactions as reported for SAAT, VAAT, CmAAT1-4, and peach ( D’Auria, 2006 ; Song et al, 2021 ). Based on this, we inferred that the difference of two conserved motifs HXXXD and LXXYYPXAGR for position X might be a main reason for the difference in esterification ability of PaAAT1-3.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the present study, PaAAT1 not only contained two common HTMCD (165–169 residues) in motif 1 and DVGWG (386–340 residues) conserved motifs in motif 7 but also contained the AAT-specific conserved motif LVYYYPLAGR (74–83 residues) in motif 8 ( Figures 1 , 2 ). Even so, residue differences might significantly alter the catalytic activity of the AAT protein and dramatically affected the esterification reactions as reported for SAAT, VAAT, CmAAT1-4, and peach ( D’Auria, 2006 ; Song et al, 2021 ). Based on this, we inferred that the difference of two conserved motifs HXXXD and LXXYYPXAGR for position X might be a main reason for the difference in esterification ability of PaAAT1-3.…”
Section: Discussionmentioning
confidence: 94%
“…All these examples illustrate the specificity in aroma production that each species can acquire while maintaining an overall ability to produce an array of esters. Peach PpAAT1 can produce esters and lactones by different acetyl ( Song et al, 2021 ). In the present study, phylogenetic analysis revealed that PpAAT1 was close to PpAAT1, and overexpression PaAAT1 led to the remarkable content increase in hexyl acetate, ( Z )-3-hexenyl acetate, and ( E )-2-hexenyl acetate.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 4 , studies on aroma metabolic pathways have preliminarily demonstrated the metabolic pathway of melon fruit aroma (Beaulieu, 2006 ; Gonda et al, 2010 ; Lange et al, 2000 ; Mayobre et al, 2021 ; Song et al, 2021 ). The precursor substance pyruvate is synthesized from glycolysis or organic acid metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is similar to that observed in previous studies examining peach fruit volatile formation [ 12 , 37 ]. According to published reports, the accumulation of γ-decalactone, which has a peach-like flavor, is highly correlated with the activities of AAT, FAD, FAH, ACX, and cytochrome P450 hydroxylases [ 12 , 16 , 27 , 38 , 39 , 40 ]. Additionally, the observed increase in the lactone content following the transient over-expression of Mi9LOX and MiEH2 reflected their probable role in the lactone biosynthesis in mango fruits [ 41 ].…”
Section: Discussionmentioning
confidence: 99%